Neoadjuvant Chemotherapy for Locally Advanced Breast Cancer: Imunohistochemical Analysis is Predicitve of Response to Chemotherapy - Herchenhorn, Daniel (2022)
Neoadjuvant chemotherapy is the standard initial treatment for locally advanced breast cancer, and correlation between response to chemotherapy and prognostic factors may be useful in this disease. From September 1996 to December 1997, 25 patients with breast cancer stage IlIA, IIIB and inflammatory were submitted to 4 cycles of neoadjuvant chemotherapy consisting of doxorubicin 60mg/m² and cyclophosphamide 600mg/² every 3 weeks, Patey mastectomy and adjuvant treatment. Clinical and pathological responses were related to biological markers studied by imunohistochemical analysis. The markers analyzed were: hormonal receptors, p53, HER/neu (cerb-B2), MIB, nuclear grade and PCNA. Objective clinicai response was 74%. Twenty one out of 23 patients (91%) were operated. Four patients had a complete response on the breast (19%), and two of them also had no axillary disease; 4 patients had residual tumor of less then 2 cm (19%). All markers were overexpressed. Overexpression of p53 and MIB on imunohistochemical analysis had an association with response to neoadjuvant chemotherapy, but it was not statistically significant. There was a positive relation between p53 and clinicai and pathological response that was not found in previous studies. Besides p53, MIB overexpression was also related to a favorable pathological response.